Gender Different Analysis in Actual Behavior of COVID-19 Prevention among College Student (Case Study: Industrial Engineering, Telkom University) - Sheila Amalia Salma; Yunita Nugrahaini Safrudin; Dino Caesaron; Tiara Verita Yestica (Jurnal Rekayasa Sistem & Industri, 2021)
Various efforts have been made by the government in reducing the number of COVID-19 cases in Indonesia,such as health intervention programs by encouraging the adaptation of new habits, such as carrying out healthprotocols which include washing hands, using hand-sanitizer, and wearing masks. To make healthintervention programs more effective and to see the importance of students as agents of change and socialcontrol, this study aims to analyze gender differences in the actual behavior of individual students inpreventing the transmission of COVID-19. This study used an online survey to a group of students (IndustrialEngineering, Telkom University) and it will be analyzed using descriptive analysis and binary logisticregression test. The results show that the gender were significantly associated with the actual behavior ofpreventing the transmission of COVID-19, through the use of hand-sanitizer (p<0.05) and washing handsevery time they left the house (p<0.05). Female students tend to have better actual behavior than malestudents. Overall, this study found that more than 90% of students reported having carried out actual COVID19 prevention behaviors well. It is hoped that these results can be used as an illustration of interested partiesto target groups of students, especially the male gender, that should be placed on providing informationrelated to COVID-19 prevention behavior.